Complement Anaphylatoxin C5a, Endothelial Dysfunction and Low-Grade Inflammation in Atherosclerotic Vascular Diseases - Shagdarsuren, Gansuvd; Khaidav, Gelegjamts; Togtokh, Ariunaaa; Sonomjamts, Munkhbayarlakh; Shagdarsuren, Erdenechimeg (Central Asian Journal of Medical Sciences, 2018)
Objectives: The objective of the paper is to summarize the evidence in atherosclerosis research regarding the relationship of complement C5a with low-grade inflammation, endothelial dysfunction, and atherosclerosis. Methods: A systematic review of the literature was performed from 1990 to 2017 regarding the contribution of the complement anaphylatoxin C5a in atherosclerosis with an emphasis on new research findings. The strategy included searching the electronic databases of Web of Science by Thomson Reuters and PubMed Central®. Results: The targeted recherché revealed a clear pro-inflammatory role of C5a in atherosclerotic vascular low-grade inflammation. Conclusion: There are clear associations between complement C5a and endothelial dysfunction in low-grade atherosclerotic inflammation. Therapeutic strategies to capture C5a or the development of pharmacomimetics of the vasoprotective endothelial phenotype appear to be a potentially fruitful strategy.